Long-Term Clinical Outcomes of Symptom Overreporting and Cognitive Underperformance in Adult ADHD Assessments - Emily Raasch; Hanna Christiansen; Johanna Kneidinger; Björn Albrecht; Anselm B. M. Fuermaier (Psychological Injury and Law, 2026)
Abstract Invalid responding can bias clinical judgement, particularly in adult attention-deficit/hyperactivity disorder (ADHD), where rates of symptom overreporting and cognitive underperformance are elevated. Performance validity tests (PVTs) and symptom validity tests (SVTs) are commonly used to assess response credibility, yet their relevance for long-term clinical outcomes in ADHD remains unclear. The present study examined whether PVT and SVT scores obtained during diagnostic assessment are associated with long-term clinical outcomes in adults with ADHD. Data were drawn from an outpatient cohort of adults diagnosed with ADHD ( N = 181). Participants completed standardised diagnostic assessment including two memory-based PVTs, one attention-based PVT, and two embedded SVTs. Long-term clinical outcomes, including psychotherapy use, pharmacotherapy, and diagnostic re-evaluation, were assessed via self-report approximately one year later. Associations were examined using correlational analyses. No significant associations were observed between PVT and SVT scores and long-term clinical outcomes. In contrast, baseline ADHD symptom ratings showed small and domain-specific associations with treatment-related outcomes. These findings suggest that validity indicators may be more relevant to proximal clinical processes than to the prediction of longer-term treatment outcomes in adult ADHD. Future research should examine how validity indicators influence decision-making and treatment processes in adult ADHD assessment, using longitudinal and multi-method designs with more sensitive outcome measures.